Facilitating renewables and power-to-gas via integrated electrical power-gas system scheduling. (1st October 2020) - Belderbos, Andreas; Valkaert, Thomas; Bruninx, Kenneth; Delarue, Erik; D'haeseleer, William
Highlights: Accommodating electricity from renewable sources leads to volatile natural gas off-take. Power-to-gas technologies strengthen the link between the power and natural gas system. We model joint scheduling decisions in the electric power system and natural gas system. We present a case study of a future Belgian power and natural gas system. Abstract: The possibly increasing volatile gas off-take from gas-fired power plants to accommodate volatile renewable generation in combination with the integration of power-to-gas (P2G) warrants further study into the operation of a coupled electrical power and natural gas system. Therefore, this paper presents and validates a novel operational model comprising both the electrical power and gas systems. Model improvements include (i) the use of zonal gas loads in addition to nodal loads, (ii) ramp rates for conventional gas production facilities and, (iii) an improved detailed technological model of P2G units, which all increase the realism of the obtained results. Results of several small-scale case studies illustrate the relevance of these model additions. In addition, a case study inspired by the Belgian electrical power and gas systems shows that the Belgian gas network has abundant capacity to integrate a possibly volatile injection of synthetic methane from P2G. This model may be used by electricity and gas transmission system operators to study the interaction between their systems and inform policy makers and regulators.